Adaptive technologies for hybrid ad-hoc/cellular network architecture. (29th July 2011) - Barnawi, Ahmed
Ad-hoc networking was brought into the scene of cellular communications on the assumption that transmissions over short links relax background interference and improve the overall performance. Ad-hoc Networking Over UMTS Protocol (ANOUP) was introduced to improve on the cellular performance. However, this improvement was shown to be limited by excessive interference and scheduling throughput delay. To enhance ANOUP performance, consideration is given to combining ANOUP's transmission strategy with adaptive wireless techniques. In this paper we focus on adaptive modulation and adaptive smart antenna system. Our results show that throughput rate can be doubled using developed cross-layer protocol design.